A behavioral investigation of supply chain contracts for a newsvendor problem in a developing economy (2019)
The business context in developing economies introduces challenges in scaling production that are often distinct from those faced in mature economies. This study focuses on the potential for risk-sharing mechanisms to overcome some of those challenges for agricultural supply chains in Uganda. The study follows a two-stage research approach conducted in collaboration with the United Nations World Food Programme (WFP), which supported adoption of hermetic crop storage products such as silos in the country since 2013. In the first stage, through interviews with six artisanal silo manufacturers we identified three constraints in scaling silo production that were accentuated by the newsvendor dynamics in this market. In the second stage, we considered the potential for risk-sharing contracts to help alleviate some of those constraints and explored behavioral explanations to account for differences. We ran a laboratory experiment using two contracts that our interviews suggest are feasible in this business context: a buyback mechanism that allows manufacturers to share the risks of procuring excess metal sheets and a salvage mechanism that allows them to share the risks of over-producing silos. The results reveal a consistent under-ordering across both contracts. They also show that while buyback participants respond to contract prices as existing theory would predict, salvage participants do not. Our study provides insights regarding the potential, and the limitations, of different risk-sharing mechanisms to increase the supply of products in developing economies. © 2019 Elsevier B.V.